Minoritas Dan Politik Perukunan (FKUB, Ideologi Toleransi dan Relasi Muslim-Kristen Aceh Tamiang) - Ismail Fahmi Arrauf Nasution (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
One concept of how to improve the relationship between Christians and Muslims is the concept of interfaith dialogue. Community must deepen their knowledge to improve interreligious relationship. Avoiding stereotypes and learning other religions will increase understanding and respect among each other thus people can live together peacefully. One organization that seeks to assist with interfaith misunderstandings and provides opportunities for interreligious dialogue is the Interfaith Communication Forum (FKUB). FKUB's goal is to "knit true brotherhood, participate to build peace", build harmonious relationships and maintain their differences through a communication